1996
DOI: 10.1016/0014-5793(96)00221-9
|View full text |Cite
|
Sign up to set email alerts
|

The N‐terminal X‐X‐Pro sequence of the HIV‐1 Tat protein is important for the inhibition of dipeptidyl peptidase IV (DP IV/CD26) and the suppression of mitogen‐induced proliferation of human T cells

Abstract: Recent data in the literature suggest that the HIV-1 Tat(I-86) protein exhibits immunosuppressive effects. Moreover, Tat was found to interact with dipeptidyl peptidase IV (DP IV), which is identical to the T cell activation marker CD26. Here we show that the N-terminal amino acid sequence of Tat is essential for the inhibition of DP IV-catalyzed IL-2(1-12) degradation. Nterminal modification of Tat with rhodamine prevented inhibition of enzymatic activity of DP IV as well as suppression of DNA synthesis of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 23 publications
(31 reference statements)
2
44
0
Order By: Relevance
“…The hydrophobic side chain would likely replace the Tat-(1-9) methionine side chain in the S1 pocket of DPPIV. This view is supported by a kinetic study showing that the peptides FAPAG, FHPKR, and IKPEA have an inhibitory potential comparable to peptides featuring an N-terminal Met (17). Peptides with Ala, Gly, or Thr in the N-terminal position lacked the ability to inhibit DPPIV and indicated that an N-terminal hydrophobic residue is a prerequisite for a peptide to act as a DPPIV inhibitor.…”
Section: Structural Data Suggest a Competitive Type Of Inhibitionsupporting
confidence: 51%
See 1 more Smart Citation
“…The hydrophobic side chain would likely replace the Tat-(1-9) methionine side chain in the S1 pocket of DPPIV. This view is supported by a kinetic study showing that the peptides FAPAG, FHPKR, and IKPEA have an inhibitory potential comparable to peptides featuring an N-terminal Met (17). Peptides with Ala, Gly, or Thr in the N-terminal position lacked the ability to inhibit DPPIV and indicated that an N-terminal hydrophobic residue is a prerequisite for a peptide to act as a DPPIV inhibitor.…”
Section: Structural Data Suggest a Competitive Type Of Inhibitionsupporting
confidence: 51%
“…6 are also well defined in the electron density, but only poor density is observed for the side chains because they do not form contacts to DPPIV. These side chains were consequently placed with the most likely conformation determined by NMR spectroscopy of peptide Trp 2 -Tat-(1-9) in aqueous solution, which indicated that the main chain conformation of this nonapeptide is determined by Pro 3 (17,34,35). It is notable that the conformation of Trp 2 -Tat-(1-9) in the NMR study is comparable to that found here for the N-terminal 6 residues of Trp 2 -Tat-(1-9).…”
Section: Methodsmentioning
confidence: 99%
“…Proteins with proline, hydroxylproline, or N-methylglycine in the third position are thought to prevent cleavage by DPP4. 43 This highlights the complexity of potential DPP4 cleavage kinetics, which may differ in vitro and in vivo, and further highlights the necessity of testing the individual DPP4 cleavage potential of each protein of interest.…”
Section: Effects Of Dpp4 On Leukocyte Trafficking and Migrationmentioning
confidence: 99%
“…The CD26 ectopeptidase inhibitor 12 13 ), antimouse CD26 (H194-112; BD Biosciences), antimouse CD3 (2C11; BD Biosciences), and antimouse CD28 (MCA1363; Serotec). The human chemokine CXCL-12 (stromal-derived factor-1␣ [SDF-1␣]) was purchased from Pepro Tech (Peterborough, United Kingdom).…”
Section: Peptides Antibodies and Reagentsmentioning
confidence: 99%
“…To exclude the possibility that CD26 signaling modified other intrinsic properties of anergic T cells, the naturally occurring peptide YY peptide containing the X-X-Pro N-terminal motif known to inhibit DPPIV enzymatic activity was also employed 12 to treat anergic T cells prior to injection (30 nM for 30 minutes at room temperature). The following day, PKH26-labeled C6 T cells (5-7 ϫ 10 6 ) were injected intraperitoneally.…”
Section: Cd26 Enzymatic Activity Mediates Inhibition Of Tissue Infiltmentioning
confidence: 99%